Evaluation of Central and Peripheral Retinal Vascular Changes in the Fellow Eyes of Patients with Unilateral Retinal Vein Occlusions - Mestan Ertop; Fulya Yaylacıoğlu Tuncay; Yavuz Kemal Arıbaş; Hüseyin Baran Özdemir; Gökhan Gürelik; Mehmet Emin Atılgan; Şengül Özdek (Türk Oftalmoloji Dergisi)

(untitled)
Objectives: To evaluate the subtle peripheral retinal and macular vascular changes in the fellow eyes of patients with unilateral retinal vein occlusion (RVO). Materials and Methods: This retrospective study included 53 patients with unilateral RVO and 44 age-matched controls. The frequency of peripheral retinal vascular pathologies in both eyes was evaluated using high quality ultra-wide field fluorescein angiography (UWFFA). Macular vascular density, flow area, and foveal avascular zone measurements from optical coherence tomography angiography (OCTA) were analyzed together with laser flare photometry values in patients and controls. Results: Peripheral retinal vascular pathologies were detected on UWFFA in the fellow eyes of 36 (67.9%) patients. No significant central vascular pathologies were detected on OCTA and there was no significant difference in OCTA parameters between the fellow eyes and the controls. Flare values did not differ significantly between the control and the fellow eyes. Conclusion: Two thirds of the fellow eyes of unilateral RVO patients had subtle peripheral retinal vascular changes, while there was no significant microvascular change detected with OCTA in the macula. This suggests that vascular changes caused by systemic vascular disorders probably first start in the peripheral retina of the fellow eyes of patients with RVO.